Effects of recreational SCUBA diving practiced once a week on neurohormonal response and myokines-mediated communication between muscles and the brain - Njire Braticevic, Marina; Zarak, Marko; Simac, Brankica; Perovic, Antonija; Dumic, Jerka (Frontiers in Cardiovascular Medicine, 2023)
During physical activity, activation of muscular, endocrine, and nervous systems, results in intensive crosstalk between muscles and other organs, which enables response to physiological stress. In SCUBA diving, extreme environmental conditions represent an additional challenge for homeostasis maintenance, but underlying mechanisms are largely unknown. We aimed to contribute to the understanding of neurohormonal response and muscle-brain crosstalk by measuring the concentrations of the selected hormones secreted by the pituitary-target organ axis and myokines involved in the muscle-brain endocrine loop in recreational SCUBA (rSCUBA) divers. Fourteen male divers performed five open-water recreational dives (one per week, depth of 20-30 m, lasting 30 min, between 9 and 10 am), after a winter non-diving period of 5 months. Blood samples were collected immediately before and after the first, third, and fifth dives. Adrenocorticotropic hormone (ACTH), cortisol, thyroid-stimulating hormone (TSH), free thyroxine (fT4), prolactin, total testosterone, growth hormone (GH), insulin-like growth factor-1 (IGF-1), irisin, brain-derived neurotrophic factor (BDNF), S100B, glial fibrillary acidic protein (GFAP), and neuron-specific enolase (NSE) were measured using commercially available immunoassays. Cortisol and ACTH levels decreased after every dive, while testosterone decreased only after the first dive. No significant changes in post-dive values, as well as the cumulative effect on other measured hormone, were observed. Although irisin and BDNF levels decreased after the first and third dives, the fifth dive caused a significant increase in both myokines. Changes in IGF-1 levels were not observed. All three dives caused a significant increase in S100B levels. A statistically significant decrease in GFAP concentration was observed after every dive, while NSE pre-dive concentration declined over the studied period. The cumulative effect on myokine levels was reflected in a continuous decline in irisin and BDNF pre-dive levels, but an increasing trend after the fifth dive was observed. Observed changes in myokines and hormone levels point to a specific response to rSCUBA practiced once a week, most likely due to extreme environmental conditions. Further studies on communication between muscles and other organ systems, particularly on the muscle-brain endocrine loop, are required for a deeper understanding of the adaptation mechanisms to this kind of physiological stress.